Implementasi FL Studio untuk Meningkatkan Pemahaman Materi Teater pada Kelas XI-1 SMAN 9 Malang : Penelitian - Ageng Wiro Leksono (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
This study aims to examine the implementation of FL Studio in enhancing the understanding of theater material among students of class XI-1 at SMAN 9 Malang. FL Studio, as a music and audio production software, is used to support theater learning by offering a creative approach through sound processing, music, and audio effects. The research method employed is a qualitative approach with a Classroom Action Research (CAR) design conducted in two cycles. Data were collected through observations, interviews, and tests of material comprehension. The results indicate that the use of FL Studio can increase students' interest and engagement in theater learning, as well as deepen their understanding of theater elements such as music, sound, and effects in theater performances. Therefore, the application of FL Studio proves effective in enriching the theater learning process in class XI-1 at SMAN 9 Malang. This study suggests the use of multimedia technology as an innovative tool in performing arts education.